Kajian Histokimia Sebaran Karbohidrat Netral Pada Usus Halus Ayam Hutan Hijau (Gallus Varius) Asal Pulau Alor - Manu, Zion Kurnia Putra Pertama; Amalo, Filphin A; Nitbani, Heni (Jurnal Veteriner Nusantara, 2024)
Green jungle fowl (Gallus varius) is a type of local chicken in Indonesia. Green jungle fowl are only found in Indonesia, which are spread from Java, Madura, Bali, Lombok, Sumba, Sumbawa, Flores and Alor. The small intestine consists of the duodenum, jejunum and ileum which function in the absorption of nutrients. Periodic Acid Schiff (PAS) is a special staining method that aims to see the characteristics of neutral carbohydrates in cells or body tissues. A positive PAS staining reaction is indicated by the presence of a magenta-red color in the examined tissue. This study aims to determine the distribution of neutral carbohydrates in the small intestine of the green jungle fowl (Gallus varius) from Alor Island. Small intestine samples were taken from 3 green jungle fowl collected in Alor District. Microscopic observation of small intestine tissue that has been stained with PAS stain. The results showed that the small intestine of the green jungle fowl consists of the duodenum, jejunum and ileum. Neutral carbohydrates are distributed throughout the tunica duodenum, jejunum and ileum with varying intensity. Moderate intensity (++) was seen in goblet cells and liberkuhn's crypts. Weak intensity (+) is seen on the surface of the epithelium, lamina propria, lamina muscularis mucosa, tunica submucosa, tunica muscularis, and tunica serosa.